Optimization of fermentation conditions of exopolysaccharide production from Saccharomyces cerevisiae YY-02 and its functional properties analysis - WANG Changli, ZHANG Cheng, BIN Xiaoyun, ZHAO Yunhui, ZHANG Yunye, YE Guangbin (Zhongguo niangzao)
Exopolysaccharide (EPS) was produced by fermentation using Saccharomyces cerevisiae YY-02 as the test strain and initial fermentation medium as the culture medium. The fermentation conditions were optimized by single factor tests and response surface tests, and the functional properties (water retention, water solubility, emulsification and antioxidant properties) of EPS were studied. The results showed that the optimal medium formula for polysaccharide production by strain YY-02 was as follows: sucrose 73 g/L, yeast extract 21 g/L, NH4Cl 2.0 g/L, KH2PO4 2.0 g/L, CaCl2 0.3 g/L. The optimal culture conditions were obtained as follows: loading liquid volume 141 ml/250 ml, inoculum 2%, initial pH 7.0, fermentation time 144 h, and temperature 30 ℃. Under this optimization conditions, EPS yield reached 4.52 g/L, which was 2.50 times more than before optimization. The contents of total sugar, uronic acid, protein and sulfate of EPS produced by strain YY-02 were 83.65%, 15.27%, 0.78% and 0.30%, respectively. The water retention (WHC) and water solubility index (WSI) were 229.67% and 75.23%, respectively. When the mass concentration of EPS was 1 g/L, the emulsification of organic phase gasoline, soybean oil, benzaldehyde and petroleum ether was more than 25%. When the mass concentration of EPS was 3 g/L, the scavenging rates of 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)(ABTS+), O2- free radical and H2O2 were the highest, which were 24.8%, 43.79% and 11.40%, respectively. Therefore, S. cerevisiae YY-02 had certain antioxidant activity.